Artifacts from American fashion - Lee, Heather Vaughan (Greenwood Press "Daily life through history" series., 2020)
"Clothing and fashion accessories can serve as valuable primary sources for learning about our history. This unique book examines daily life in twentieth-century America through the lens of fashion and clothing"--